1989
DOI: 10.1203/00006450-198905000-00016
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Predicting Energy Requirements of Children during Catch-Up Growth Developed Using Doubly Labeled Water

Abstract: ABSTRACT. Energy partitioned to maintenance plus activity, tissue synthesis, and storage was measured in 41 children in early recovery [W/L (wtllength) < 5th percentile] from severe protein-energy malnutrition and in late recovery (WIL = 25th percentile) to determine energy requirements during catch-up growth. Metabolizable energy intake was measured by bomb calorimetry and metabolic collections. Energy expended (i f SD) for maintenance and activity estimated by the doubly labeled water method was 97 2 1 2 kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…16 Fjeld et al propose a carefully validated model based on data from children recovering from malnutrition which suggests that 733 kJ/kg/day should affect growth rates of about 10 g/kg/day. 17 Growth rates of 7-15 g/kg/day have been reported from well functioning inpatient therapeutic feeding centres. 9 17 18 The modest growth rate seen in this study may suggest that there is sharing of the RTUF at home with other family members.…”
Section: Discussionmentioning
confidence: 99%
“…16 Fjeld et al propose a carefully validated model based on data from children recovering from malnutrition which suggests that 733 kJ/kg/day should affect growth rates of about 10 g/kg/day. 17 Growth rates of 7-15 g/kg/day have been reported from well functioning inpatient therapeutic feeding centres. 9 17 18 The modest growth rate seen in this study may suggest that there is sharing of the RTUF at home with other family members.…”
Section: Discussionmentioning
confidence: 99%
“…A review of studies from Europe and North America found little evidence of adverse effects of low dietary fat on growth of young children aged 6 to 36 months. The percentage of dietary fat was not correlated with growth velocity or energy density of the diet between ages 6 and 12 months, whereas energy density of the diet was positively associated with energy intake and weight gain (Fjeld et al, 1989, Butte, 1996, Nicklas et al, 1992, Shea et al, 1993. No association between fat intake and growth was detected in infants aged 7 to 13 months or children aged 2 to 5 years or 3 to 5 years (Friedman and Goldberg, 1976;Lapinleimu et al, 1995, Michaelsen andJorgensen, 1995).…”
Section: Infants and Childrenmentioning
confidence: 99%
“…Beginning with the morning following the isotope administration, daily urine samples were collected for the next 7 days with the time of the sample collection being recorded. This 7 day period represents 2 to 3 biological half-lives of the isotopes in the body determined by water turnover (Fjeld et al 1989;Roberts et al, 1988). The urine samples were analyzed for isotopic enrichment relative to local standard by isotope-ratio mass spectrometry (Aqua-Sira model; VG Isogas, Cheshire, UK).…”
Section: Methodsmentioning
confidence: 99%